2021
DOI: 10.1111/mec.15787
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide single nucleotide polymorphism markers reveal population structure and dispersal direction of an expanding nuisance algal bloom species

Abstract: Species invasion and range expansion are currently under scrutiny due to increasing anthropogenic impact on the natural environment. This is also true for harmful algal blooms, which have been reported to have increased in frequency. However, this research is challenging due to the ephemeral nature, small size and mostly low concentrations of microalgae in the environment. One such species is the nuisance microalga Gonyostomum semen (Raphidophyceae), which has increased in occurrence in northern Europe in rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…Most previous studies also revealed that outcrossing of plants from the locations of origin (North Carolina, Georgia, and Florida in the US) of S. alterniflora generated a genetic admixture, and genetic variation remained high compared to those in the native populations ( Bernik et al, 2016 ; Qiao et al, 2019 ; Xia et al, 2020 ). Moreover, only the TG and CX populations had higher expected heterozygosity ( He , 0.145 and 0.115) than observed heterozygosity ( Ho , 0.121 and 0.110), which may have been a reflection of earlier population bottlenecks ( Rengefors et al, 2021 ), whereas, other populations did not show evidence of bottlenecks. Therefore, neither of the two Spartina species in China showed the genetic paradox of invasion.…”
Section: Discussionmentioning
confidence: 78%
“…Most previous studies also revealed that outcrossing of plants from the locations of origin (North Carolina, Georgia, and Florida in the US) of S. alterniflora generated a genetic admixture, and genetic variation remained high compared to those in the native populations ( Bernik et al, 2016 ; Qiao et al, 2019 ; Xia et al, 2020 ). Moreover, only the TG and CX populations had higher expected heterozygosity ( He , 0.145 and 0.115) than observed heterozygosity ( Ho , 0.121 and 0.110), which may have been a reflection of earlier population bottlenecks ( Rengefors et al, 2021 ), whereas, other populations did not show evidence of bottlenecks. Therefore, neither of the two Spartina species in China showed the genetic paradox of invasion.…”
Section: Discussionmentioning
confidence: 78%
“…Alternatively, bead-beating of cells in a mixer mill can be employed to isolate nuclei. This method was particularly successful in the raphydophyte Gonyostomum semen [30]. In many cases, however, enzymatic treatment to disrupt cell walls needs to be implemented before protoplast content extraction [4,11,31].…”
Section: Obtaining Biomassmentioning
confidence: 99%
“…In studies on microalgae, commonly-used buffers are LB01 (with streptophytes, Chlorophyta, Ochrophyta, raphidophytes; [4,11,30]), a MOPS-based buffer (3-(N-morpholino) propanesulfonic acid (used with dinoflagellates; [21,24]), or Otto buffers (with chrysophytes; [16,29]). Triton X-100 (to a final concentration of 0.05%-1%) may be added to improve the sample staining, though its effect varies across different groups of algae [2,7,14,19,34].…”
Section: Isolation Buffersmentioning
confidence: 99%
“…Genomic DNA was digested with high-fidelity SbfI (New England Biolabs), applying a RAD library preparation protocol modified from Amores et al (2011) and Etter et al (2011). Modifications (according to Rengefors et al, 2021) included an increased amount of ligase (2000 U µl -1 T4 ligase) and decreased volume of NEB2 buffer (1 µl).…”
Section: Rad Library Preparationsmentioning
confidence: 99%